Optimization of dose and image quality in CR and DR for common digital radiographic examinations - Moey, Soo Foon; Sayed, Inayatullah Shah; Zubir, Ahmad Shazli (2017)
A fine balance of image quality and radiation dose can be achieved by optimization to minimize stochastic and deterministic effects. This study aimed in ensuring that images of acceptable quality for common radiographic examinations in digital imaging were produced without causing harmful effects. The study was conducted in three phases. The pre-optimization involved ninety physically abled patients aged between 20 to 60 years and weighed between 60 and 80 kilograms for four common digital radiographic examinations. Kerma X_plus, DAP meter was utilized to measure the entrance surface dose (ESD) while effective dose (ED) was estimated using CALDose_X 5.0 Monte Carlo software. The second phase, an experimental study utilized an anthropomorphic phantom (PBU-50) and Leeds test object TOR CDR for relative comparison of image quality. For the optimization phase, the imaging parameters with acceptable image quality and lowest ESD from the experimental study was related to patient’s body thickness. Image quality were evaluated by two radiologists using the modified evaluation criteria score lists. Significant differences were found for image quality for all examinations. However significant differences for ESD were found for PA chest and AP abdomen only. The ESD for three of the examinations were lower than all published data. Additionally, the ESD and ED obtained for all examinations were lower than that recommended by radiation regulatory bodies. Optimization of image quality and dose was achieved by utilizing an appropriate tube potential, calibrated automatic exposure control and additional filtration of 0.2mm copper.